GRAMMATICAL TYPES OF COMPARATIVE CONSTRUCTIONS IN THE POETRY OF B. PASTERNAK (American Journal of Interdisciplinary Research and Development, 2025)
The article analyzes the specifics of grammatical structures of various types of constructions with comparative semantics in the poetry of B. Pasternak as a characteristic feature of his idiostyle and individual-authorial linguistic worldview. Comparison is considered as a special method of artistic interpretation of reality and one of the most significant means of artistic expressiveness in the poet’s creative work.